Pulpal and periodontal diseases increase triglyceride levels in diabetic rats - Cintra, Luciano Tavares Angelo [UNESP]; da Silva Facundo, Aguinaldo Cândido [UNESP]; Azuma, Mariane Maffei [UNESP]; Sumida, Doris Hissako [UNESP]; Astolphi, Rafael Dias [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Narciso, Luís Gustavo [UNESP]; Gomes-Filho, João Eduardo [UNESP] (Springer Nature, 2013)
Objectives: The aim of this study was to evaluate triglyceride and cholesterol levels in diabetic rats and their relationship with pulpal and periodontal diseases. Methods: Eighty male rats (Rattus norvegicus albinus, Wistar) were divided into the following eight groups comprising ten animals each: normal rats (G1), rats with pulpal diseases (G2), rats with periodontal diseases (G3), rats with both pulpal and periodontal diseases (G4), diabetic rats (G5), diabetic rats with pulpal diseases (G6), diabetic rats with periodontal diseases (G7), and diabetic rats with both periodontal and pulpal diseases (G8). Diabetes was induced by injecting streptozotocin, periapical lesions were induced by exposing pulpal tissue to the oral environment, and periodontal diseases were induced by periodontal ligature. The animals were killed after 30 days, and lipid profile was enzymatically measured using Trinder's method. The total assessed values were statistically analyzed by analysis of variance and Tukey test (p < 0.05). Results: The triglyceride levels of diabetic rats with periodontal disease and of diabetic rats with both periodontal and pulpal diseases were significantly higher than those of normal rats and nondiabetic group rats, respectively. The differences in the cholesterol levels among the groups were not significant. Conclusions: We found that the association of pulpal and periodontal diseases with diabetes increased triglyceride levels in rats. Clinical significance: Changes in lipid profile may be related to the presence of oral infections and diabetes. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Cholesterol levels; Diabetes; Lipid profile; Oral infections; Triglyceride levels